Bimbingan dan Konseling terhadap Peningkatan Pengetahuan dan Sikap Remaja Putri tentang Personal Hygiene saat Menstruasi - Yusmaneli Yusmaneli; Dilgu Meri; Hirza Rahmita; Wira Ekdeni Aifa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of guidance and counseling on improving adolescent girls' knowledge and attitudes regarding personal hygiene during menstruation at SMP Negeri 3 Sungai Lala, Indragiri Hulu Regency. The method used was a quantitative study with a pre-experimental design using a one-group pretest-posttest. The results showed an increase in adolescent girls' knowledge and attitudes following guidance and counseling. The Wilcoxon Signed Rank Test yielded p-values of 0.000 for knowledge and 0.007 for attitude (p < 0.05). In conclusion, guidance and counseling significantly improved adolescent girls' knowledge and attitudes regarding personal hygiene during menstruation at SMP Negeri 3 Sungai Lala, Indragiri Hulu Regency. Keywords: Guidance, Counseling, Knowledge, Personal Hygiene, Attitude